La festividad de la Mamacha del Carmen en Paucartambo como espacio de resistencia ante la mirada secularizadora del mundo - Revilla Valdivia, Camila (Pontificia Universidad Católica del Perú, 2026)
This essay examines how the festivity of the Virgin of Carmen in Paucartambo emerges as a space of resistance against secularizing perspectives that have established antithetical boundaries between the religious and the political, the public and the private. It argues that this celebration reconfigures such premises by intervening in the public sphere, inscribing its own political subjectivity within a collective narrative, and adapting to modernization processes that, rather than dissolving its socio-spiritual identity, ultimately strengthen it. Within this framework, the study seeks to identify the main propositions of the secularization paradigm in order to develop a well-founded critique from the standpoint of popular religion, understood through a situated interpretive approach focused on the lived experiences of participants and the internal dynamics of festive sequences within patronal celebrations. To this end, a literature review is conducted to contextualize the study, clarify key concepts—secularization and popular religion—and provide theoretical grounding for the findings. The discussion then turns to the contemporary context of Paucartambo, integrating visual records as complementary interpretive resources aimed at more deeply representing the tensions and meanings inherent in religious experience. Ultimately, this essay concludes that the symbolic reaffirmation of Paucartambo’s socio-spiritual identity subverts epistemic hierarchies and affirms the persistence of worldviews in which the sacred and the political are interwoven in ways that the secular paradigm fails to fully grasp.

El presente ensayo analiza cómo la festividad de la Virgen del Carmen en Paucartambo se erige como un espacio de resistencia ante las perspectivas secularizadoras que han preceptuado límites antitéticos entre lo religioso y lo político, lo público y lo privado. Se plantea que esta fiesta reconfigura dichos postulados al irrumpir en el espacio público, inscribir su propia subjetividad política en una narrativa colectiva y al adaptarse a los procesos de modernización que, lejos de diluir su identidad socioespiritual, la fortalecen. En este marco, se busca identificar los principales planteamientos del paradigma de la secularización con el fin de desarrollar una crítica fundamentada desde la perspectiva de la religión popular, entendida a partir de un enfoque interpretativo situado, centrado en la experiencia de los sujetos participantes y los procesos propios de las secuencias festivas al interior de las fiestas patronales. Para ello, se lleva a cabo una revisión bibliográfica que permite contextualizar el estudio, esclarecer los conceptos clave —secularización y religión popular— y sustentar teóricamente los hallazgos. Posterior-mente, se desarrolla una discusión que sitúa el contexto contemporáneo de Paucartambo e incorpora, de manera complementaria, registros visuales como recursos interpretativos que están orientados a representar con mayor profundidad las tensiones y significados de la experiencia religiosa. Finalmente, este ensayo concluye que la reafirmación simbólica de la identidad socioespiritual paucartambina subvierte jerarquías epistémicas y reafirma la vigencia de cosmovisiones donde lo sagrado y lo político se entrelazan de formas que el paradigma secular no logra aprehender en toda su complejidad.
The festivity of Mamacha Carmen as a space of resistance against the secularizing gaze of the world
Keywords: Religious syncretism; Secularization paradigm; Modernity; Popular religion; Political agency; Sincretismo religioso; Paradigma de la secularización; Modernidad; Religión popular; Agencia política; https://purl.org/pe-repo/ocde/ford#5.04.01